2003
DOI: 10.1002/jctb.841
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wastewater using a combined biological and electrochemical technique

Abstract: Simulated wastewater containing propylene glycol methyl ether, Ni 2+ and Zn 2+ was treated using an aerated packed column. An electrochemical cell was also installed beneath the packing support in the bottom section of the column. The flowrate of water through the column was maintained at 8.94 kg m −2 s −1 . For 72 h of treatment using aeration alone, the BOD 5 was reduced by 43%, 56%, and 54% for air flowrates of 0.00094, 0.00141, and 0.00188 kg m −2 s −1 respectively. On the other hand, when the electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…Zn 2+ removal was more favourable at this pH. This was also observed by others such as Simonsson 22 and Doan et al 8 The standard reduction potential of Zn 2+ is greater than that of Ni 2+ , implying that Ni 2+ should be reduced more readily than Zn 2+ . However, the results obtained showed that Zn 2+ was actually removed to a greater extent than Ni 2+ .…”
Section: +supporting
confidence: 71%
See 1 more Smart Citation
“…Zn 2+ removal was more favourable at this pH. This was also observed by others such as Simonsson 22 and Doan et al 8 The standard reduction potential of Zn 2+ is greater than that of Ni 2+ , implying that Ni 2+ should be reduced more readily than Zn 2+ . However, the results obtained showed that Zn 2+ was actually removed to a greater extent than Ni 2+ .…”
Section: +supporting
confidence: 71%
“…A similar observation was also reported by several researchers who worked in treating dilute metallic wastewater. 8,17,18 In the electrodeposition of metal ions using insoluble anodes, the bulk pH usually decreases owing to the electrolysis of water releasing H + into the solution. 19 Under neutral and acidic conditions the electrolysis of water at the anode can be described as 20…”
Section: +mentioning
confidence: 99%
“…Doan et al studied the effect of the electrolyte pH on Zn(II) and Ni(II) binary electrodeposition. The data indicated that the best metal deposition occurred at an electrolyte pH of about 6.0 . Likewise, Orhan et al studied nickel deposition from an aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…A feed tank was filled with an electrolyte solution (the concentrated Zn-Ni metals solution from biosorbent regeneration), and 1000 ppm of potassium chloride was added, as a supporting electrolyte, to enhance the electric current flow. The electrolyte pH was maintained at 5.5 -6.0 over the experiment duration (Simonsson, 1984;Orhan et al, 2002;Doan et al, 2003).…”
Section: Metal Recovery By Electro-deposition Processmentioning
confidence: 99%
“…The electrolyte pH is one of the most important factors that have a crucial effect on the metal removal. Doan et al (2003) studied the effect of the electrolyte pH on Zn 2+ and Ni 2+ binary electro-deposition. The data indicated that the best metal deposition occurred at an electrolyte pH of about 6.0.…”
Section: Zn-ni Electro-deposition Recovery Processmentioning
confidence: 99%